MODERN CONCEPTS ABOUT THE PATHOGENESIS OF ENDOGENOUS INTOXICATION IN ACUTE PNEUMONIA IN YOUNG CHILDREN (World Bulletin of Public Health, 2023)
For quite a long time, various aspects of the diagnosis and prognosis of pneumonia in young children continue to remain an urgent problem in clinical pediatrics [1, 2]. Thus, according to WHO, this pathology is one of the main causes of infant and child mortality. More than a million children die annually due to pneumonia, which corresponds to a figure of 17.5% in the structure of deaths of children under 5 years of age [3]. For clinicians and researchers, the problem of the growing number of complicated forms of pneumonia among young children remains relevant.
Keywords: Pneumonia; respiratory failure; endogenous intoxication